Performing hackathons as a way of positioning boundary organizations. Issue 3 (9th May 2016) - Seravalli, Anna; Simeone, Luca
Abstract : Purpose: – The purpose of this paper is to compare two boundary organizations situated in Malmö (Sweden) and oriented toward opening production. Particularly, it looks at how the two organizations tried to establish and communicate their boundaries during their official opening events, which were structured according to the format of hackathon. Design/methodology/approach: – The authors adopted an ethnographic approach and followed the two events, observing and interacting with organizers and participants. The findings reported here draw upon data collected through direct observation, the authors' experience as participants, unstructured conversations, e-mail exchanges. Findings: – This paper analyzes the two events in order to show how different cultures of opening production lead to different ways of performing hackathons and, consequently, how these events affect the process of establishing and communicating the organizational boundaries. Originality/value: – The paper looks at the potential of events structured according to the format of hackathon as a way for boundary organizations to position themselves.